Oxidative damage and antioxidant defense in Caiman latirostris (Broad-snouted caiman) exposed in ovo to pesticide formulations - Burella, Pamela Mariana (2018)
The surface used for agricultural production in Argentina significantly increased in recent years, mainly due to the expansion of soybean crops. As a result, the use of agrochemicals increased too. Many natural populations of Caiman latirostris (broad-snouted caiman) are affected by habitat fragmentation and the constant exposure to pesticides. This exposure could produce Reactive Oxygen Species. The negative imbalance between ROS generation and the capacity of the biological systems to eliminate the reactive intermediaries or avoid the damage is called Oxidative Stress. The aim of this study was to evaluate oxidative damage and antioxidant defense in C. latirostris hatchlings after in ovo exposure to widely used pesticide formulations. Embryos were exposed by topical exposure on the eggshell, from the beginning of incubation period, to sub-lethal concentrations of two glyphosate formulations: PanzerGold® (PANZ) and Roundup® Full II (RU): 500, 750, 1000 μg/egg; to the endosulfan (END) formulation Galgofan® and the cypermethrin (CYP) formulation Atanor®: 1, 10, 100, and 1000 μg/ egg. Blood samples were taken to all animals immediately after hatching for the application and comparison of the following oxidative stress biomarkers between the exposed groups and their respective controls: lipoperoxidation through thiobarbituric acid reactive substances (TBARS), DNA base oxidation through the modified comet assay, and the activities of Catalase (CAT) and Superoxide dismutase (SOD) in erythrocytes. Our results showed lipoperoxidation in caiman exposed to END (10, 100, 1000 µg/egg), CYP (1, 10, 1000 µg/egg), RU (500, 1000 µg/egg) and PANZ (500, 1000 µg/egg), DNA base oxidation in those exposed to END (10, 100, 1000 µg/egg), CYP (1, 10 µg/egg) and PANZ (500, 750 µg/egg) as well as alteration in the activity of SOD in END 1 µg/egg and CYP (10, 1000 µg/egg). This study demonstrated the incidence of oxidative stress in animals exposed to pesticide formulations widely used in agricultural activity associated mainly with soybean crops, and add further information to that previously reported about pesticide effects in this native reptile species.